2006
DOI: 10.1002/jnr.20741
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte differentiation is increased in transferrin transgenic mice

Abstract: Transferrin (Tf), the iron transport glycoprotein found in biological fluids of vertebrates, is synthesized mainly by hepatocytes. Tf is also synthesized by oligodendrocytes (Ol), and several lines of evidence indicate that brain Tf could be involved in myelinogenesis. Because Tf is postnatally expressed in the brain, we sought to investigate whether Tf could intervene in Ol differentiation. For this purpose, we analyzed transgenic mice overexpressing the complete human Tf gene in Ol. We show that the hTf tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…The Tf can selectively regulate MBP expression at the transcriptional level and increase the differentiation, maturation and myelination of OLs (EspinosaJeffrey et al 2002;Sow et al 2006). Thus, our finding that high expression of Tf in OLs is consistent with previous report.…”
Section: Candidate Genes That May Intrinsically Control Ol-specific Dsupporting
confidence: 92%
“…The Tf can selectively regulate MBP expression at the transcriptional level and increase the differentiation, maturation and myelination of OLs (EspinosaJeffrey et al 2002;Sow et al 2006). Thus, our finding that high expression of Tf in OLs is consistent with previous report.…”
Section: Candidate Genes That May Intrinsically Control Ol-specific Dsupporting
confidence: 92%
“…However, most of the soluble iron in any biological system is in the ferrous form, and would have to be converted to ferric iron before it would bind to Tf. The elevated production of myelin is consistent with elevated myelination associated with over-expression of Tf by oligodendrocytes (Saleh et al, 2003, Sow et al, 2006.…”
Section: Transferrin: Role In Iron Import and Myelinationsupporting
confidence: 50%
“…The hypermyelinating effect of transferrin overexpression had no effect on mouse locomotion, cognitive and emotional abilities, and electron microscopic analysis showed myelin of normal thickness and compaction (Saleh et al, 2003). Using the same mouse model, Sow et al (2006) showed that OPCs cultured from brains of these mice show accelerated differentiation [expression of O4 and PLP markers (O4 and O1, markers of pro-oligodendrocytes)] as well as increased expression of Sox 10 and Olig1 mRNA and protein. These observations suggest that the overexpression of transferrin in oligodendrocytes in this model stimulates accelerated differentiation (i.e., earlier production of normal myelin), but not necessarily more myelin.…”
Section: Transferrin: Role In Iron Import and Myelinationmentioning
confidence: 93%
“…Of note, an increase in CSF asialotransferrin to transferrin ratio has been reported in patients with congenital disorders of glycosylation since these disorders have been recognized. 30 There is increasing evidence that transferrin plays a role in oligodendrocyte maturation and homeostasis, [31][32][33][34][35][36][37] in addition to its known role in iron metabolism and oxidative stress. 38 Thus, decreased asialotransferrin to transferrin ratio in the CSF may simply be a manifestation of disturbed protein homeostasis within the CNS as a result of EIF2B mutations, or it may play a role in the pathophysiology of the disorder.…”
Section: Discussionmentioning
confidence: 99%